Activation of an imprinted Igf 2 gene in mouse somatic cell cultures. - Eversole-Cire, P (1993)
The mouse insulin-like growth factor II gene (Igf 2), located on distal chromosome 7, is parentally imprinted such that the paternal allele is expressed while the maternal allele is transcriptionally silent. We derived a cell line from a mouse embryo maternally disomic and paternally deficient for distal chromosome 7 (MatDi7) to determine the stability of gene repression in culture. MatDi7 cells maintained Igf2 in a repressed state even after immortalization, except for one randomly picked clone which spontaneously expressed the gene. Igf 2 was expressed in a cell culture derived from a normal littermate; this expression was growth regulated, with Igf 2 mRNA levels increasing in the stationary phase of growth. Analysis of the methylation status of 28 sites distributed over 10 kb of the gene did not show consistent differences associated with expression level in the normal and MatDi7 cell lines, and the CpG island in the Igf 2 promoter remained unmethylated in all of the cell lines. Only with an oncogenically transformed cell line did the promoter become extensively methylated. We attempted to derepress the imprinted gene in MatDi7 cells by treatments known to alter gene expression. Expression of the Igf 2 allele in MatDi7 cells was increased in a dose-dependent manner by treatment with 5-aza-2'-deoxycytidine or bromodeoxyuridine, agents known to change DNA methylation patterns or chromatin conformation. Treatment of the cells with 1-beta-D-arabinofuranosylcytosine, 2'-deoxycytidine, calcium ionophore, heat shock, cold shock, or sodium butyrate did not result in increases in the levels of Igf 2 expression. It seems likely that the mechanism of the Igf 2 imprint involves subtle changes in the methylation or chromatin conformation of the gene which are affected by 5-aza-2'-deoxycytidine and bromodeoxyuridine.